The Associations Between Social Media Use with Eating Behavior, Physical Activity, and Nutrition Status among Adolescents in DKI Jakarta: Hubungan Pola Penggunaan Media Sosial dengan Perilaku Makan, Aktivitas Fisik, dan Status Gizi pada Remaja di DKI Jakarta - Amalia, Salsabila Nur Idzhni; Octaria, Yessi Crosita; Maryusman, Taufik; Imrar, Iin Fatmawati (Universitas Airlangga, 2023)
Background: Increased adolescent social media use can lead to lower physical activity. In addition, the growth of marketing of unhealthy foods and drinks is inevitable. In short, excessive social media use may negatively impact nutrition problems, eating behavior, and physical activities. Objectives: This study aimed to determine the relationship between patterns of social media use and nutrition status, eating behavior, and physical activity among adolescents in DKI Jakarta. Methods: The study was cross-sectional and involved 187 students from public high schools in Jakarta. Data was collected using the Food Frequency Questionnaire (FFQ), the International Physical Activity Questionnaire (IPAQ), the use of social media questionnaire, and an anthropometric assessment to measure body mass index for age. The statistical analysis used was the chi-square test. Results: No significant association were found between the frequency and duration of social media use and nutrition status. The type of exposure to social media content does not show a significant relationship with nutrition status, eating behavior, and physical activity. However, there were significant associations between frequency (p=0.022) and duration (p=0.003) of social media use and eating behavior. Likewise, there was a significant relationship between frequency (p=0.021) and duration (p=0.005) of social media use with physical activity. Conclusions: Duration and frequency of social media use are associated with riskier eating patterns and lower adolescent physical activity. Therefore, nutrition education in adolescents should also include topics on social media use.